2020
DOI: 10.2151/jmsj.2020-012
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characteristics of Pre-summer Rainfall over South China and Associated Synoptic Conditions

Abstract: Climatological characteristics of pre-summer (April-to-June) rainfall over Southern China (SC) and associated synoptic conditions are examined using 1980-2017 hourly rainfall observations and reanalysis data. The rainfall amount, frequency, and intensity show pronounced regional variations and substantial changes between pre-and post-monsoon-onset periods. Owing to more favorable thermodynamic conditions after monsoon onset over South China Sea (SCS), rainfall intensifies generally over entire SC irrespective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 49 publications
7
53
0
Order By: Relevance
“…The importance of tropical‐originating airflows in the BL and lower troposphere, not necessarily reaching an LLJ's minimum intensity (peak wind speed >10 m s −1 ), in generating inland and coastal heavy rainfall over south China during presummer rainy season (April–June) has recently been documented in the literature (Chen et al, 2017; Huang & Luo, 2017; Li et al, 2020; Wang et al, 2014). A few case studies have shown the significant contributions of coupled SLLJ and BLJ to the development of dual coexisting rainbelts, that is, with extensive heavy rainfall over inland and concurrent extreme (yet localized) coastal rainfall (Du & Chen, 2018; Shen et al, 2020; Zhang & Meng, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The importance of tropical‐originating airflows in the BL and lower troposphere, not necessarily reaching an LLJ's minimum intensity (peak wind speed >10 m s −1 ), in generating inland and coastal heavy rainfall over south China during presummer rainy season (April–June) has recently been documented in the literature (Chen et al, 2017; Huang & Luo, 2017; Li et al, 2020; Wang et al, 2014). A few case studies have shown the significant contributions of coupled SLLJ and BLJ to the development of dual coexisting rainbelts, that is, with extensive heavy rainfall over inland and concurrent extreme (yet localized) coastal rainfall (Du & Chen, 2018; Shen et al, 2020; Zhang & Meng, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Du and Chen (2018, 2019a) pointed out that, for coexisting inland synoptic and coastal warm‐sector heavy rainfall over south China, an SLLJ and a BLJ are more closely related to the former and latter, respectively. Climatological analyses (Li et al, 2020; Zhang & Meng, 2019) and another case study (Shen et al, 2020) confirm that the coupling of BLJs and SLLJs favors the initiation of coastal convection leading to warm‐sector heavy rainfall over south China through BL convergence and lower level to midlevel divergence. Differences between the BLJ and SLLJ influencing rainfall over south China are also noticed in terms of their spatial distributions and associated physical mechanisms (Du et al, 2014; Du & Chen, 2019b).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…During the warm season, an abundance of organized storm types is observed, such as long‐lived mesoscale convective systems (Huang, Liu, et al, 2019), squall lines (Meng et al, 2013), supercells, and tornadoes (Bai, Meng, et al, 2020). As a result, monsoon rainfall exhibits a complex spatiotemporal nature along the coasts of South China (e.g., Chen et al, 2018; Li et al, 2020). In particular, the pronounced subseasonal/diurnal variations in convection and rainfall are demonstrated to be highly related to the summer monsoon, complex terrains (island, peninsula, and mountain), and land‐sea breeze circulations (e.g., Chen, Zhao, & Xue, 2014; Houze et al, 1981; Luo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The convergence can be enhanced when the BLJ collides with the coastal mountains and produces strong boundary-layer upward motion, providing favorable conditions for the initiation of the OWSRs on the windward side of the coastal mountains. This mechanism has been demonstrated for a heavy warm-sector rainfall at the coast of South China by Du and Chen [44] and a large ensemble of rainfall events over South China coasts during Apr-Jun 1980-2017 by Li et al [78]. Regarding the ACR situation, the boundary-layer convergence between northerly and southeasterly winds near the coastal mountains that form under this type likely promotes the initiation of the coastal OWSRs (Figure 8b).…”
Section: Synoptic Situation Extension and Orientation Of The Coastamentioning
confidence: 61%